Utility of noninvasive biomatrices in pharmacokinetic studies†. (13th August 2013) - Raju, Kanumuri Siva Rama; Taneja, Isha; Singh, Sheelendra Pratap; Wahajuddin
ABSTRACT: Blood and plasma are the biomatrices traditionally used for drug monitoring and their pharmacokinetic profiling. Blood is the circulating fluid in contact with all organs and tissues of body and thus is the most representative fluid for measuring systemic drug levels. However, venipuncture suffers from the caveat of being an invasive technique which often makes people reluctant to participate in clinical studies. Thus, there is a need for noninvasive bio‐fluids that are ethically appropriate, cost‐efficient and toxicologically relevant. These alternate bio‐fluids may prove clinically useful as alternatives to plasma/serum in therapeutic drug monitoring, pharmacokinetic and toxicokinetic studies, doping control in sports medicine and to monitor local adverse effects. These may be of particular interest in the case of special population groups such as neonates, children, the elderly, terminally ill patients and pregnant or lactating women, and offer the advantage of circumvention of the demand for specialized personnel for sample collection. This review describes such noninvasive bio‐fluids (saliva, sweat, tears and milk) that have been considered for pharmacokinetic drug analysis, emphasizing their sample preparation, its associated difficulties and their correlation with plasma. Copyright © 2013 John Wiley & Sons, Ltd.